Fechamento de escolas do campo no brejo paraibano: resistência e permanência - Silva, José Rogério da (2023)
Our research focuses on the theme of Rural Education, guided by the precursors of the discussion, namely: Arroyo (1999, 2000, 2004, 2006, 2007, 2011); Caldart (1997, 2000, 2004, 2009); Fernandes (2004, 2006); Molina 2004, 2009) and Souza (2006), our research problem is based on the following question: In what context did the resistance of the São José do Bonfim community to the threat of closing the Municipal School Maria Emília Maracajá take place? We chose as genera l objective: To understand the process of resistance of the São José do Bonfim Community, through the imminent threat of closure of the M unicipal School Maria Emília Maracajá. It also specifically seeks: Understanding the context in which the closure of ru ral schools occurs, in the municipality of Areia Paraíba; Analyze the context of resistance of the São José do Bonfim Community against the closing of the Maria Emília Maracajá Municipal School; Investigate the contribution of teachers and social movemen ts in the process of resistance and permanence of the activities of the Municipal School Maria Emília Maracajá. Methodologically, we have a qualitative approach, of the Case Study type, a Document Analysis was carried out exploring the entire context of th e closure of rural schools in the researched locus. Semi structured interviews were carried out, involving four subjects who experienced the entire phenomenon researched, from a perspective of Historical dialectical Materialism. Among the findings of the r esearch it is visualized that: The Municipality of Areia Paraíba adopted the policy of closing schools inserted in the field, between the years 2011 and 2016, seventeen schools were closed in the field. We explored the resistance of the São José do Bonfi m community to the closure of the Maria Emília Maracajá Municipal School, as an exercise in resistance motivated by the desire to change the social reality in which they were inserted. The stru ggle undertaken leads to the consequent permanence of the activ ities of that school, generating great repercussions in the media, social movements and local society. This research results in the Master's Dissertation of the Graduate Program in Education at the Education Center of the Federal University of Paraíba, lin ked to the line of research: Teaching and Learning Processes.